A maximum power point tracking method with variable weather parameters based on input resistance for photovoltaic system. (December 2015) - Li, Shaowu
Highlights: A MPPT method with VWP based on input resistance is proposed. This method is considered specially from input resistance of PV system standpoint. The control signal can be directly calculated out by this method after S, T and RL have measured. The relationships between weather parameters ( S and T ) and Vm, Im are found out. Abstract: In order to greatly improve the maximum power point tracking (MPPT) speed and adaptability to the varying weather conditions for photovoltaic (PV) system, in this paper, a MPPT method with variable weather parameters (VWP) considered specially from input resistance standpoint is proposed. As well as other VWP methods, it can also track the maximum power point (MPP) as quickly as possible. In this method, the approximate relationship between control signal and PV cell parameters ( Vm and Im ) is firstly built by studying the input resistance of PV system deeply, then the relationship between VWP and Vm, Im is found by the curve fitting technique. Through these relationships, the bridge between control signal and VWP is built successfully, which is the key work to implement the direct MPPT control. Finally, some simulation experiments show that the proposed method is feasible and available to track the MPP successfully and has better MPPT rapidity, accuracy, stability and adaptability than conventional perturbation and observation (P&O) method and fuzzy control method.